Konsep Pendidikan Citra Universiti: Satu Pengenalan (The Concept of Citra Education: An Introduction) - Ahmad Jamsari Alias (MALIM: Jurnal Pengajian Umum Asia Tenggara, 2016)
Education need to be dynamic in nature and changes are inevitable in the forms of curriculum, its methodologies as well as its teaching and learning orientation. In today’s context, global development along with the Industrial Revolution 4.0 and its automation surroundings put a great challenge againts human capabilities and demands. These environments create extensive impacts on the way how people learn and acquire knowledge, managing information, and other related skills particularly in the orbit of Higher Learning Institutions (HLIs) and universities. Previous researches suggest that unemployabilities are related to lack of soft-skills such as communication, leadership, innovation, creativity, and manners due to irrelevant process of true education. Realizing this urgent needs, Universiti Kebangsaan Malaysia through Pusat Citra Universti has answer it by introducing a new concept of education. This fresh concept of Citra Education is developed from a series of thorough researches, discussions among stakeholders and other parties, scutinuzing on the components of new teaching and learning techniques, as well as analyzing liberal educations formats around the world which have been in practiced in international universities. This resulted into the establishment of the Concept of Citra Education by Pusat Citra Universiti, UKM which consits of Six Main Domains of Citra Utama that is Citra 1 Etika, Kenegaraan dan Ketamadunan, Citra 2 Bahasa, Komunikasi dan Literasi, Citra 3 Penaakulan, Kuantitatif dan Kualitatif, Citra 4 Kepimpinan, Keusahawanan dan Inovasi, Citra 5 Sains, Teknologi dan Kelestarian, and Citra 6 Kekeluargaan Kesihatan dan Gaya Hidup. All these six Citra offer various courses that equip students with relevent knowledge, information, and skills with freedom of choices among students in selecting their subjects based on their interest and industrial needs.